A novel heterozygous mutation (γIIe367Thr) causes congenital dysfibrinogenemia in a Chinese family. Issue 8 (December 2020) - Luo, Shasha; Xu, Qiyu; Xie, Yaosheng; Li, Xiaolong; Jin, Yanhui; Yang, Lihong; Liu, Siqi; Wang, Mingshan
Abstract : N/A: The aim of this study was to elucidate the molecular defects in a Chinese family with dysfibrinogenemia. The fibrinogen activity was measured by the one-stage clotting method. The fibrinogen antigen was measured with immunoturbidimetry. The fibrinogen gene was amplified by PCR with direct sequencing. Suspected mutation was confirmed by reverse sequencing. Bioinformatics and model analysis were used to study the conservatism and harm of the mutation. The proband had a history of menorrhagia. Study showed fibrinogen activity at 0.35 g/l and fibrinogen antigen at 2.05 g/l. Sequencing analysis detected a heterozygous c.1178T>C missense mutation in exon 9 of FGG gene resulting in p.IIe367Thr. The bioinformatics and model analysis indicated that the IIe367Thr mutation may disrupt the activation of the fibrinogen. We detected a novel IIe367Thr missense mutation in the FGG . To our knowledge this is causative mutation has not been reported so far.